2020
DOI: 10.3390/s20216052
|View full text |Cite
|
Sign up to set email alerts
|

Design, Validation and Comparison of Path Following Controllers for Autonomous Vehicles

Abstract: As one of the core issues of autonomous vehicles, vehicle motion control directly affects vehicle safety and user experience. Therefore, it is expected to design a simple, reliable, and robust path following the controller that can handle complex situations. To deal with the longitudinal motion control problem, a speed tracking controller based on sliding mode control with nonlinear conditional integrator is proposed, and its stability is proved by the Lyapunov theory. Then, a linear parameter varying model pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It can be seen that it is necessary to correct the front wheel angle value of the intelligent vehicle, so as to ensure that the intelligent vehicle runs on the predetermined path [10]. The above Figure 6 shows the model of Stanley compensatory pure pursuit and following control algorithm, establishing the coordinate system, and (𝑥 ,𝑦 )为 is the center of the rear axle of the smart car; (𝑥 ,𝑦 )为 is the center of the front axle of the intelligent vehicle; 𝑝 ,𝑝 is the preview point on the desired path; 𝑉 is the longitudinal speed of the intelligent vehicle; 𝑒 is the lateral deviation between the center of the front axle and the desired path; 𝜃 is the desired heading angle; 𝛿 is the front wheel angle value; 𝑅 is the distance between the rear axle center and the circular motion center; 𝑑 is the lateral distance between the preview point and the circular motion center, which is obtained from the mathematical theorem:…”
Section: Improvement Of Pure Pursuit Control Algorithmmentioning
confidence: 99%
“…It can be seen that it is necessary to correct the front wheel angle value of the intelligent vehicle, so as to ensure that the intelligent vehicle runs on the predetermined path [10]. The above Figure 6 shows the model of Stanley compensatory pure pursuit and following control algorithm, establishing the coordinate system, and (𝑥 ,𝑦 )为 is the center of the rear axle of the smart car; (𝑥 ,𝑦 )为 is the center of the front axle of the intelligent vehicle; 𝑝 ,𝑝 is the preview point on the desired path; 𝑉 is the longitudinal speed of the intelligent vehicle; 𝑒 is the lateral deviation between the center of the front axle and the desired path; 𝜃 is the desired heading angle; 𝛿 is the front wheel angle value; 𝑅 is the distance between the rear axle center and the circular motion center; 𝑑 is the lateral distance between the preview point and the circular motion center, which is obtained from the mathematical theorem:…”
Section: Improvement Of Pure Pursuit Control Algorithmmentioning
confidence: 99%
“…For example, Kang et al proposed an improved selfadverse control (IADRC) method, including an improved extended state observer and an LQR-based error compensator, and designed a vehicle path tracking controller based on IADRC considering lateral stability, and the simulation results showed that the controller has better path tracking effect and robustness against disturbances [87].Yun et al proposed a new method for high-speed Wang et al proposed an ANN-based ADRC method for high-speed automatic emergency vehicle avoidance technology, and the simulation results proved that the method has better path tracking accuracy and robustness at different vehicle speeds, and the tracking error is smaller at 60 km/h lateral wind interference at 100 km/h vehicle speed [88].Wang et al proposed an integrated feedforward-feedback and ADRC compensation lateral control algorithm and achieved better tracking effect and stability [89]. And Yang et al verified that the tracking performance of nonlinear ADRC is slightly worse, but it has strong robustness [90].…”
Section: Adrc Algorithmmentioning
confidence: 99%
“…The control of a vehicle's motion is a critical part of autonomous vehicles, as it directly impacts the vehicle's safety and the satisfaction of its passengers. So, it is crucial to develop a path-following controller that overcomes problems in challenging environments [1].…”
Section: Introductionmentioning
confidence: 99%